IMPLEMENTATION OF AN ENERGY-EFFICIENT ALGORITHM TO IMPROVE THE ENERGY OF LOW ENERGY NODES IN WSN (International Journal of Engineering and Computer Science, 2017)
A wireless sensor network consists of a number of sensors which are interlinked for performing the same function collectively or cooperatively for checking and balancing the environmental factors. Due to their small size, they have a number of limitations. The energy constraint sensor nodes in sensors networks operate on limited power resources, so it is very important to improve energy efficiency and reduce power consumption. There are many routing protocols that have been proposed to achieve this. The adaptive routing protocols are very attractive because the routing overhead is low in their case. As a result, the routes tend to have the shortest hop count and contain weak links. They degrade the performance and are susceptible to breaks. Here, an energy efficient algorithm that is intended to provide a reliable transmission environment with low energy consumption is proposed. This algorithm efficiently utilizes the energy that is available and the received signal strength of the nodes to identify the best possible route to the destination. Simulation